Old Age in the New Land The American Experience since 1790 - Achenbaum, W. Andrew (Johns Hopkins University Press, 1978)
Drawing on a wide range of sources from social, intellectual, and political history, W. Andrew Achenbaum analyzes the changing fates and fortunes of America's elderly in the course of its history. By providing a historical perspective on society's conceptions of aging-and its effects on human lives-Achenbaum's work offers valuable insights for historians, sociologists, gerontologists, and others interested in the "graying" of America.